Road safety: Challenges and opportunities in Latin America and the Caribbean - Sebastian Martinez; Raul Sanchez; Patricia Ya\~nez-Pagans (Latin American Economic Review, 2019)
An estimated 1.3 million people die in traffic accidents each year worldwide and millions more are injured, with developing countries disproportionately affected. It is predicted that the number of global traffic deaths will be around 1.8 million annually by 2030, making it the eight cause of death in the world. This paper provides an overview of salient road safety issues in the Latin America and Caribbean (LAC) region. It also reviews existing theoretical and causal empirical evidence of interventions to improve road safety outcomes, concentrating on three core areas: safer roads and mobility, safer vehicles, and safer road users. Despite the existence of potentially cost-effective and life-saving interventions, there is surprisingly little rigorous evidence on the effectiveness of road safety programs in the LAC context. This paper discusses promising areas for policy experimentation and future research.
Keywords: R41; R42; L92; I15; K32; 330; Road safety; Road trafc accidents; Road fatalities; Latin America and the Caribbean